The Effect of Giving Avocado Leaf and Seed Extract as Antidiabetes: A Systematic Literature Review - Nurdin Rahman (Fakultas Kedokteran Universitas Sultan Ageng Tirtayasa, 2023)
This literature review aimed to determine the effect of giving avocado leaf extract and seeds as an antidiabetic. The literature study was conducted by choosing an experimental research design using experimental animal subjects. The results of a review of 9 articles showed that avocado seed and leaf extract as antidiabetics were that both of them showed potential as promising antidiabetic agents. Research on avocado seed extract showed that administration of avocado seed extract positively improved glycemic control and reduced diabetes symptoms in diabetic rats. On the other hand, research on avocado leaf extract showed that administration of avocado leaf extract could also reduce blood glucose levels and regulate lipid profiles in diabetic rats. These two extracts show different but consistent effects in improving blood glucose regulation and lipid profiles in diabetic conditions. Avocado seed extract showed a more significant effect in reducing diabetes symptoms, while avocado leaf extract showed promising potential in regulating blood glucose levels and lipid profiles